PERSISTENSI LABA DAN EKSPEKTASI INVESTOR PADA PERUSAHAAN DENGAN BOOK-TAX DIFFERENCES - Tjandra, Grace Setiyani; Lindrawati, Lindrawati; Tedjasuksmana, Budianto (Jurnal Akuntansi Kontemporer, 2013)
Quality earnings is defined as the earnings persistence because earnings persistence is a value-relevant characteristic of earnings, which is predictive value. Earnings persistence is an accounting profit that is expected in the future and could be pro-jected by the current earnings and it is determined by the components of accruals and cash flows. Book-tax differences could rep-resent the discretion of management in the accrual process, which could establish the earnings quality. This research is aimed to investigate companies with large book-tax differences have earnings persistence, accrual and cash flow are lower compared with companies that have small book-tax differences. Moreover, it also has the purpose to examine investors’ expectation towards ac-counting profit persistence that is reflected in the share price for accrual components in each sub sample of book-tax differences. As earnings persistence is equal to the expected future earnings, therefore, there are two elements that could represent the earnings persistence itself. The first one is the future change in pretax earnings and the second one is the net earning. Hence, this research has also the purpose to test the effect of a permanent and a temporary differences in the book-tax differences towards the earning’s growth. The objects of the research are 30 manufacturing companies, which have been registered in Indonesia Stock Exchange in the year of 2005 to 2010, using the purposive sampling technic. The hypotheses’ examination is using the double linear regression. The result of the research shows that companies with large positive (negative) book-tax differences have an indifferent persistence component of earning compared with companies with small book-tax differences. Furthermore, there are no proves that the share price could reflect the consistency of earning, accrual and cash flow. However, investors have the tendency to be pessimistic to-wards the relation of current earning and future earning. In other words, earning is assumed to have low persistence in every sub sample of book-tax differences. Permanent differences are not significantly xix affect earnings growth, while temporary differ-ences are significant affect earnings growth.